Critical Discourse Analysis of the Forms of Referential Power in Kike Wadatsumi no Koe's Diary - Ismi Prihandari; Roslina Bt Mamat; Ismi Prihandari; Roslina Bt Mamat (Universitas Negeri Malang, 2027)
This research aims to describe the forms of power discourse through hegemony representations in diary Kike Wadatsumi no Koe . This research uses a critical qualitative approach. Data analysis techniques are done by reading the data source, documenting the research data, and taking notes the research data includes descriptions, interpretations, and explanations according to the CDA Fairclough model. Data validation is using an intense discussion with competent experts, in addition to figure a triangulation used on data sources and triangulation between researchers. Data are collected into 13 corpus data. The results has shown power discourse form relates to the dominance of military leadership through policies adopted and efforts to utilize human resources that are trusted and made role models of Japanese society in attractting sympathy and trust from soldiers. The soldiers were invited to understand, and remembered the norms and rules applied in military world life. Finally, the soldiers can accept it as a natural thing.